(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
Clinical forensic medicine includes a wide range of procedures from examination of victims of injuries, sexual assault victim/ accused examination, custodial torture victims to much more. A wide range of clinical forensic works are done by clinical specialists including the medical, obstetric, surgical and orthopaedic experts. Standardisation of reports, improving consistency and quality of opinions prepared by experts will facilitate better delivery of justice. Formulating standard operating procedures for use in clinical forensic medicine is therefore the need of the hour.